PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENINGKATAN LABA PERUSAHAAN DI SAMARINDA - Rifadin Noor; Marwanto Marwanto; Besti Wahyu (Jurnal Eksis, 2019)
The research aims to analyse and prove the partial influence and simultaneous influence of transparancy, accountability, responsibility, indepen-dency, fairness.The research method uses a survey method, there are 30 respondents. Data collection using poll. The collected Data was analyzed using classical assumption test techniques, research hypothesis testing using multiple regression analyses with IBM SPSS Statistics 25 for Windows. The results of this study show that partial transparency has a positive and insignificant effect on the increase in profit, accountability positively and insignificant effect on increased profit, negative responsibility and insignificant to profit, independency positively and insignificant influence on profit, fairness positively and insignificant influence on profit. The simultaneous Good Corporate Governance jointly affects the increase of profit. Keywords: Good Corporate Governance, Transparancy, Accountability, Responsibility, Independency, Fairness, Profitabi.